Novel small molecule modulators of quorum sensing in avian pathogenic Escherichia coli (APEC). Issue 1 (31st December 2018) - Helmy, Yosra A.; Deblais, Loic; Kassem, Issmat I.; Kathayat, Dipak; Rajashekara, Gireesh
ABSTRACT: Colibacillosis caused by avian pathogenic E. coli (APEC), is an economically important bacterial disease of poultry. APEC are a subgroup of extra intestinal pathogenic E. coli (ExPEC) and poultry are considered potential sources of foodborne ExPEC to humans. Currently, APEC infections in poultry are controlled by antibiotics and/or vaccination; however, their effect is limited due to emergence of antibiotic resistant strains and infections with heterologous serotypes. Therefore, novel approaches are needed. Here, using the bioluminescent quorum sensing (QS) autoinducer 2 (AI-2) indicator Vibrio harveyi BB170, we screened the cell free culture supernatant of APEC O78 prepared from cultures grown in the presence of 4, 182 small molecules (SMs; 100 μM). A total of 69 SMs inhibited > 75% of APEC O78 AI-2 activity in the indicator bacteria. Ten SMs that showed highest AI-2 inhibition were selected for further studies. Most of these SMs inhibited the AI-2 activity of other APEC serotypes and significantly reduced APEC O78 biofilm formation and motility. Most compounds showed minimal toxicity on human intestinal cells (Caco-2), chicken macrophage (HD-11), and chicken and sheep red blood cells, and reduced APEC survival in HD-11 and THP-1 macrophages. The SMs induced no or minimal toxicity and conferred protection against APEC in wax moth larval model. SMs affected the expression of APEC O78 QS, virulence, biofilm and motility associated genes providing insight on their potential mode(s) of action. Further testing in chickens will facilitate development of these SMs as novel therapeutics to control APEC in poultry and thereby also reduce zoonotic transmission.